2010
DOI: 10.1111/j.1559-1816.2010.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

When Cross‐Examination Offends: How Men and Women Assess Intrusive Questioning of Male and Female Expert Witnesses

Abstract: Personally intrusive questioning during cross‐examination has become commonplace. The differential impact of this questioning on female vs. male experts was the focus in this study, thus these questions are referred to as gender‐intrusive questions. The results demonstrated that the female expert was rated as less confident, trustworthy, likable, believable, and credible than the male expert. The male and female experts were both rated as more credible, trustworthy, and believable when subjected to gender‐intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…The case was identical to the one used by Larson and Brodsky (), in which the defendant's paranoid delusional break had led to a first‐degree murder charge after the man killed his wife, son, and niece. He then called the police.…”
Section: Results From Larson and Brodsky ()mentioning
confidence: 97%
See 2 more Smart Citations
“…The case was identical to the one used by Larson and Brodsky (), in which the defendant's paranoid delusional break had led to a first‐degree murder charge after the man killed his wife, son, and niece. He then called the police.…”
Section: Results From Larson and Brodsky ()mentioning
confidence: 97%
“…Our purpose at this point is to summarize our prior related research on gender and intrusive questioning of experts before we report on our present investigation of how well different expert responses work in these situations. In our 2010 study about response style to intrusive questions and gender of the expert (Larson & Brodsky, ), we hypothesized that in general female experts would be perceived as less likeable, trustworthy, knowledgeable, and confident than comparable male experts, but that the opposite effect would be found when the mock jurors were women.…”
Section: Results From Larson and Brodsky ()mentioning
confidence: 99%
See 1 more Smart Citation
“…Some main effect findings regarding men and women experts have been uncovered. For example, Larson and Brodsky () exposed mock jurors to a videotaped summary of a criminal murder trial and an excerpt of a cross‐examination of a forensic mental health expert. They found a main effect advantage favoring male experts over female experts.…”
Section: Effects Of Expert Witness Gendermentioning
confidence: 99%
“…In the only study to examine experimentally whether intrusive questioning impacts the credibility ratings of an expert, Larson and Brodsky () found that regardless of type of questioning (intrusive or non‐intrusive), female experts were thought to be less credible than male experts. Surprisingly, mock jurors also rated the expert who was asked intrusive questions as being more believable, trustworthy, and credible.…”
Section: Role Of Expert Witnessesmentioning
confidence: 99%